From the Principle of Inertia to the Death Drive: The Influence of the Second Law of Thermodynamics on the Freudian Theory of the Psychical Apparatus - Tran The, Jessica; Ansermet, Jean-Philippe; Magistretti, Pierre; Ansermet, François (Frontiers in Psychology, 2020)
In the Freudian theory of the psychical apparatus, the introduction from the 1920s onwards of the second drive dualism appears as a major turning point. The idea of a ‘death drive’, first expressed in Beyond the Pleasure Principle (Freud, 1920g), is generally considered to be a new concept, one that represents a break with Freud’s previous thinking. It has often surprised the scholars because it seemed, at first sight, difficult to reconcile with the idea of the singularity of living organisms within which the psychical functions form an integral part. Our research aims to demonstrate that the theory of the death drive does not represent a complete change in direction for Freud. It is present, in essence, in his earliest work, to the extent that the ‘principle of inertia’ described in 1895 in A Project for a Scientific Psychology. (Freud, 1895a) can be seen as a precursor to the death drive. Based on a reading of Freud’s early formulations of his ideas, we aim to bring to light how certain aporias that seem inherent to the concept of the death drive can be overcome if we consider them in the context of an epistemological model that draws on the paradigms of physics which were conveyed by the Helmholtz School. Namely, we can consider the idea of death drive in reference to the principle of entropy and the laws of thermodynamics.